Science for a Green New Deal connecting climate, economics, and social justice - Davidson, Eric A. (Tantor Media, Inc., 2022)
Since it was first proposed in the US House of Representatives, the Green New Deal has been hotly debated. The intent was not simply to fight climate change or address a specific environmental concern, but rather to tackle how climate change and other environmental challenges affect the economy, the vulnerable, and social justice-and vice versa. In Science for a Green New Deal, Eric Davidson dissects this legislative resolution. He also shows how green new deal thinking offers a framework for a convergence of the natural sciences, social science, economics, and community engagement to develop holistic policy solutions to the most pressing issues of our day. Davidson weaves the case for linkages among multiple global crises, including a pandemic that has reversed progress on fighting poverty and hunger, an acceleration of climate change, and a renewed awareness of profound social injustices highlighted by the Black Lives Matter movement. Illustrating these points with his personal life experiences as a child growing up in Montana and as a famed researcher leading a large scientific society, Davidson relates these complex challenges to our everyday lives and decision-making. Science for a Green New Deal is a realistic and optimistic look at how we can attain a more sustainable, prosperous, and just future.
Online resource; title from title details screen (O'Reilly, viewed July 27, 2022)
Keywords: Environmental quality; Green New Deal; Sustainability; Social justice; Environnement; Qualité; Pacte vert; Durabilité de l'environnement; Justice sociale; Downloadable audio books; Audiobooks; Livres audio